TINGKAT PENGETAHUAN MASYARAKAT TENTANG KLASIFIKASI ISTILAH KASUS PASIEN COVID-19 (STUDI DESKRIPTIF) - Eka Putri Prima Sari; Dian Furwasyih; Refki Riyantori (STIKes MERCUBAKTIJAYA, 2021)
COVID-19 or Corona Virus Disease-19 is a disease that caused by a new type of corona virus. In March 2020 WHO declared a pandemic COVID-19. In Indonesia, cases of COVID-19 were first reported on March 2, 2020 and until September, 2020 it has passed 200,000 confirmed cases. Poor health literacy, coupled with the absence of synergy and the lack of knowledge regarding the COVID-19 outbreak made the handling of the outbreak carried out by the government stutter. One of the important information for the general public is the definition of the terms cases related to COVID-19. This study aims to determine the level of public knowledge about the definition of case terms related to COVID-19. Data dollection was done online by using google form. The sampling technique was quota sampling, the response rate (RR) of this study was 91% of the target 100 samples. Data were analyzed using IBP SPSS Statistic version 10. The results obtained were related to 5 questions regarding the definition of the terms PPT, OTG, ODP, PDP and confirmation cases, respondents gave the percentage of correct answers below the average (62.4%) percentage of the overall questions. A massive education is needed considering the low level of public knowledge about the issues in this research. It takes cross-sectional and cross-programmatic collaboration to solve this problem quickly.